(untitled) (gjstudies, 2017)
This research paper investigates the historical evolution of auditing standards from asocio-technical systems perspective, arguing that traditional linear models of standardsdevelopment inadequately capture the complex, recursive interplay between professional norms, technological affordances, and regulatory pressures. We propose a novelmethodological framework, termed the ’Assurance Practice Feedback Loop Model’(APFLM), which conceptualizes standards evolution not as a series of discrete updates but as a continuous, adaptive system shaped by the very assurance practicesthey seek to govern. The study employs a mixed-methods approach, combining a qualitative historical discourse analysis of key standard-setting pronouncements from 1970to 2004 with a quantitative analysis of a unique longitudinal dataset tracking changesin audit program structure and testing focus across 150 audit firms over a 15-year period. Our findings reveal a previously under-theorized ’practice-led innovation’ pathway, where emergent audit methodologies developed in response to client-specific risks(particularly in nascent technology sectors circa the late 1990s) subsequently exertedsignificant, formalizing pressure on broad standards. We identify a critical inflectionpoint around the period 1998-2002, where the lag between novel practice emergenceand standards codification shortened dramatically, fundamentally altering the ecologyof assurance. The paper concludes that this accelerated, practice-informed evolutionhas paradoxically increased both the robustness and the fragility of the financial reporting ecosystem, creating a more responsive framework while simultaneously elevatingsystemic dependencies on continuous professional judgment and tacit knowledge. Thisresearch contributes an original theoretical lens for understanding regulatory changeand offers practical insights for standard-setters navigating the integration of futuretechnological disruptions into the audit paradigm.